Chronic symptoms in patients with unilateral vestibular hypofunction: systematic review and meta-analysis - Karabulut, Mustafa; Van Laer, Lien; Hallemans, Ann; Vereeck, Luc; Van Rompaey, Vincent; Viechtbauer, Wolfgang; Melliti, Ali; van Stiphout, Lisa; Mohamad, Alfarghal; Pérez Fornos, Angélica; Guinand, Nils; van de Berg, Raymond (Frontiers in Neurology, 2023)
Objective To systematically evaluate the full spectrum of self-reported chronic symptoms in patients with unilateral vestibular hypofunction (UVH) and to investigate the effect of interventions on these symptoms. Methods A systematic review was conducted following the guidelines of the Preferred Reporting Items for Systematic Review and Meta-Analysis Statement (PRISMA). A literature search was performed in Pubmed, Web of Science, Embase, and Scopus to investigate self-reported symptoms and self-report questionnaires in patients with UVH. All original studies ranging from full-text clinical trials to case reports, written in English, German, and French, were included. The frequency of self-reported symptoms was presented. For self-report questionnaires, a meta-analysis was carried out to synthesize scale means by the pre- and post-intervention means and mean changes for studies that investigated interventions. Results A total of 2,110 studies were retrieved. Forty-seven studies were included after title-abstract selection and full-text selection by two independent reviewers. The symptoms of UVH patients included chronic dizziness (98%), imbalance (81%), symptoms worsened by head movements (75%), visually induced dizziness (61%), symptoms worsened in darkness (51%), and oscillopsia (22%). Additionally, UVH could be accompanied by recurrent vertigo (77%), tiredness (68%), cognitive symptoms (58%), and autonomic symptoms (46%). Regarding self-report questionnaires, UVH resulted on average in a moderate handicap, with an estimated mean total score on the Dizziness Handicap Inventory (DHI) and the Vertigo Symptom Scale (VSS) of 46.31 (95% CI: 41.17–51.44) and 15.50 (95% CI: 12.59–18.41), respectively. In studies that investigated the effect of vestibular intervention, a significant decrease in the estimated mean total DHI scores from 51.79 (95% CI: 46.61–56.97) (pre-intervention) to 27.39 (95% CI: 23.16–31.62) (post intervention) was found (p < 0.0001). In three studies, the estimated mean total Visual Analog Scale (VAS) scores were 7.05 (95% CI, 5.64–8.46) (pre-intervention) and 2.56 (95% CI, 1.15–3.97) (post-intervention). Finally, a subgroup of patients (≥32%) persists with at least a moderate handicap, despite vestibular rehabilitation. Conclusion A spectrum of symptoms is associated with UVH, of which chronic dizziness and imbalance are most frequently reported. However, semi-structured interviews should be conducted to define the whole spectrum of UVH symptoms more precisely, in order to establish a validated patient-reported outcome measure (PROM) for UVH patients. Furthermore, vestibular interventions can significantly decrease self-reported handicap, although this is insufficient for a subgroup of patients. It could therefore be considered for this subgroup of patients to explore new intervention strategies like vibrotactile feedback or the vestibular implant. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42023389185].